Avaliação do efeito do óleo essencial de Citrus Auratium L. no infarto do miocárdio em ratos - Polo, Celi Macedo [UNESP] (2014)
The effect of treatment with Citrus aurantium essential oil (OEC) on rat models of experimental myocardial infarct was evaluated. Rats were treated with OEC 250mg/kg (p.o.) for 7 days and the infarct was induced by isoproterenol administration (100mg/kg, sc) on treatment days 6 and 7. Twenty four hours after the second isoproterenol injection the rats were killed and the enzymatic, serum, heart morphological and functional parameters were evaluated. Isoproterenol administration increased significantly the level of biochemical markers of myocardial (CK-MB, total cholesterol), liver (AST, ALT) and kidney (urea, creatinine) injury and induced myocardial damage and necrosis as evaluated by histopathological evaluation and TTC staining, respectively. No functional impairment was observed in the Langendorff perfused rat hearts from isoproterenol-treated animals. The OEC treatment was not able to prevent or attenuate the isoproterenol-induced myocardial lesion or any of the biochemical and morphological changes accompanying the infarct. In addition, hearts from OEC treated rats were not protected from the myocardial lesion induced by in vitro ischemia-reperfusion. The results obtained in the two different models of myocardial infarct show that OEC (250mg/kg) administration has no cardioprotective effect